Systematic Literature Review on Financial Constraints and Their Impact on Corporate Innovation - Pratama, Sari Indra; Rosalina, Rita (Library of Sultan Agung Islamic University, 2025)
Financial constraints are a major obstacle in the corporate innovation process, especially related to limited access to capital for research and development (R&D) investment. This has implications for the company's low innovation capacity and competitiveness in a competitive global market. The purpose of this research is to systematically review the literature related to the influence of financial constraints on corporate innovation, as well as identify the role of public policy and management strategies in overcoming these obstacles. The method used is systematic literature review (SLR) with a qualitative approach, following the PRISMA 2020 guidelines, as well as manual content analysis of selected articles from Scopus indexed journals for the 2024-2025 period. The data consisted of five scientific articles relevant to the keywords